THE ASYMMETRIC EFFECTSOF MACROECONOMIC VARIABLES ON THE NIGERIAN STOCK MARKET - Sabo, Ahmed Yusuf; Yola, Abdulnasir T.; Jakada, Aminu Hassan; Ahmed, Bello Abba (Kashere Journal of Management Sciences, 2025)
Nigeria’s pursuit of economic growth has led to increased reliance on fossil fuels for energy generation, resulting in significant carbon emissions that negatively impact environmental quality. This study examines the effect of carbon dioxide (CO₂) emissions on environmental quality in Nigeria. Using secondary data spanning from 1992 to 2022, sourced from the World Development Indicators (WDI, 2023) and the U.S. Energy Information Administration (EIA, 2024), the study employs the Autoregressive Distributed Lag (ARDL) model for analysis. The results confirm strong evidence of cointegration between CO₂ emissions and environmental quality. Both long-run and short-run estimates reveal that energy consumption from petroleum and other liquids has a positive and significant relationship with carbon emissions. Based on these findings, the study recommends that Nigerian policymakers adopt and implement sustainable energy policies and technologies aimed at reducing carbon emissions. Furthermore, greater investment in renewable energy sources such as solar, wind, tidal, and geothermal energy is encouraged to ensure a cleaner and healthier environment.